Lutte Contre La Déscolarisation Dans L’enseignement Primaire : Les Cantines Scolaires En Côte d’Ivoire - Toure Krouélé (European Scientific Journal, ESJ, 2017)
This article is a research on the contribution of the school canteens in the fight against the deschooling in primary education in Côte d’Ivoire. Statistical data are analyzed and investigations by talks are carried out with samples of teachers and advisors in canteens. The results show that in spite of the persistence of deschooling in the primary education, the establishment of the canteens obeys a policy of targeting. The questioned actors however underline the importance of these canteens in the retention and the success of the pupils in primary cycle. Actually, the impact of the canteens on schooling in the primary education is limited by the weak national cover in canteens and the dysfunctions which characterize their management.